"Comparative Analysis of the Initial Concept of the Method of Collaborative Learning with the Modern Method" - Anvarjonkizi, Erkinova Solokhidinova Ra’nokhon (International Journal of Human Computing Studies, 2022)
The article describes the concepts of collaborative learning methods, in their initial use and in modern ones, besides that the main advantages of the Collaborative Learning method.